Low-iron-content boat support for photovoltaics and semiconductors and manufacturing method of low-iron-content boat support

By using a specific process to prepare low-iron-content silicon carbide boat supports, the problems of high iron content and serious pollution of traditional silicon carbide boat supports have been solved, resulting in silicon carbide boat supports with high flexural strength and long lifespan, which are suitable for the photovoltaic and semiconductor industries.

CN119285360AInactive Publication Date: 2025-01-10SHENYANG XIKA FINE CERAMICS CO LTD

Patent Information

Application Number
CN202411392204.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional quartz boat supports are prone to deformation and have a short service life under high temperature conditions. The iron content of silicon carbide boat supports is difficult to control, leading to silicon wafer contamination. Existing silicon carbide boat supports have high iron content and serious contamination.

Method used

Using green silicon carbide powder and ultrapure carbon black as raw materials, a slurry is prepared by ball milling, and after being cast into shape, it is purified and sintered at high temperature in an induction furnace. Subsequently, it is siliconized and sintered at high temperature in a vacuum furnace. Combined with specific process treatment, the iron content is controlled to prepare a low-iron-content silicon carbide boat support.

Benefits of technology

The prepared silicon carbide boat support has high flexural strength and low iron content, meeting the lifespan and pollution-free requirements of the photovoltaic and semiconductor industries, extending its service life and reducing the risk of silicon wafer contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005072734960000181
    Figure BDA0005072734960000181
Patent Text Reader

Abstract

The manufacturing method comprises the following steps that S1, raw materials, an organic auxiliary agent and pure water are subjected to slurry preparation in a ball milling tank according to the proportion, a boat support splitting part blank is obtained through a slip casting technology, and a boat support splitting part blank is obtained; performing natural drying and hot air drying on the green body to discharge moisture, and then fettling and carving the green body into a boat support splitting part semi-finished product meeting the size requirement; s2, putting the semi-finished product in S1 into an induction furnace, purifying and sintering at high temperature of 2000-2300 DEG C under the protection of inert gas, and obtaining a silicon carbide boat support splitting part biscuit which has the open pore porosity of 8-10% and the strength of more than 70 Mpa and contains a small amount of free carbon after high-temperature purifying and sintering; and S3, splicing the silicon carbide boat support splitting part biscuits, feeding the spliced whole boat support into a vacuum furnace, carrying out high-temperature siliconizing sintering treatment at 1650-1700 DEG C, and carrying out grinding, sand blasting, fine cleaning, impurity removal, ultrasonic cleaning and drying process treatment after discharging to obtain the low-iron-content boat support.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of boat support manufacturing, and in particular to a low-iron content boat support for photovoltaics and semiconductors and a manufacturing method thereof. Background Art

[0002] The boat support is a key bearing component of the diffusion process equipment in the photovoltaic and semiconductor industries. Its application in the photovoltaic and semiconductor industries is mainly in the production process of photovoltaic cells, as a carrier for photovoltaic cells. In the photovoltaic and semiconductor industries, the traditional boat support material is mainly quartz, but because the quartz boat support is easy to deform in high temperature environment and has a short service life of about 3-6 months, silicon carbide boat support, as a new type of boat support material, has gradually become the preferred boat support material in the photovoltaic and semiconductor industries due to its good thermal stability and long service life.

[0003] Silicon carbide has excellent high temperature resistance and corrosion resistance, and its strength is high. Due to the chemical properties of silicon carbide ceramics, it is difficult to form, so it is usually prepared by reaction sintering. The reaction sintering method includes the steps of powder preparation, block pressing, drying and sintering. These steps involve many parameters. For example, the powder preparation stage requires a reasonable ratio of raw materials and the preparation of powder with a compliant particle size. The block pressing stage requires reasonable pressure conditions and block size design, and the temperature setting and processing time setting of the drying and sintering stages. If these steps are not designed reasonably, it will affect the hardness and other indicators of the finished product.

[0004] Silicon carbide boat supports can replace quartz boat supports and have a longer service life of more than 5 years. The use of silicon carbide boat supports can significantly reduce the cost of use, reduce downtime caused by maintenance and repairs, and reduce production capacity losses. Silicon carbide, as the main raw material for making silicon carbide boat supports, has properties such as high strength, high elastic modulus, high thermal expansion coefficient, good thermal shock resistance and acid and alkali corrosion resistance. Due to these excellent properties, silicon carbide materials are often used in industrial fields such as microelectronics, mechanical seals, aerospace, and heat exchange. Silicon carbide micropowder, which is the raw material used to prepare silicon carbide ceramics, has a significant effect on the various properties of silicon carbide ceramics after sintering. In order to obtain silicon carbide ceramics with excellent performance, manufacturers have put forward strict requirements on the particle size, particle shape, purity and fluidity of silicon carbide powder.

[0005] The photovoltaic and semiconductor industries usually use quartz as boat supports to support wafer boats. Silicon wafers are loaded on the wafer boats for diffusion, coating and annealing processes. As the industry's requirements for the performance and efficiency of silicon wafers become increasingly stringent, rapid heat treatment technology has been widely adopted, and increasingly stringent requirements have been placed on the carrying kiln tools. Quartz boat supports are rarely used, have a short lifespan and are easily damaged, so they are gradually being replaced by silicon carbide boat supports with better performance. Although the bearing strength and lifespan of traditional reaction-sintered silicon carbide boat supports can meet industry requirements, their impurity content, especially the iron content, is difficult to control. A large number of applications have shown that the iron content in the reaction-sintered silicon carbide boat supports will contaminate the silicon wafers, causing the color of the silicon wafers to darken and become scrapped. Therefore, it is particularly important to seek a low-iron content boat support and a manufacturing method for photovoltaics and semiconductors. Summary of the invention

[0006] In order to solve the problems mentioned in the above background technology, the present invention provides a low iron content boat support for photovoltaics and semiconductors and a manufacturing method thereof.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for manufacturing a low-iron-content boat support for photovoltaics and semiconductors comprises the following steps:

[0009] S1. Prepare slurry by mixing raw materials, organic additives and pure water in a ball mill according to a certain proportion, and obtain a blank of the boat support split component by a slip injection molding process. After the blank is naturally dried and dried with hot air to remove moisture, it is trimmed and carved into a semi-finished boat support split component that meets the size requirements;

[0010] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;

[0011] The organic additive is a mixture of a binder, a dispersant and a defoamer;

[0012] S2, putting the semi-finished product in S1 into an induction furnace, and sintering it at a temperature of 2000-2300° C. under the protection of an inert gas to obtain a green blank of a silicon carbide boat support split component having an open porosity of 8-10%, a strength greater than 70 MPa, and containing a small amount of free carbon;

[0013] S3. The split blanks of the silicon carbide boat support are spliced ​​together. After being spliced ​​into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1650-1700°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.

[0014] Preferably, the mass ratio of the raw material, the organic additive and pure water is (160-170):(6-8):(3-5).

[0015] Preferably, the green silicon carbide powder is mixed with green silicon carbide powder having three particle size distributions of average particle size of 90 to 100 μm, 8 to 10 μm and 1.5 to 2.5 μm;

[0016] The mass ratios of green silicon carbide powder with three particle size distributions to ultrapure carbon black are controlled within the range of [(30-35):(15-20):(47-50)]:(2-3).

[0017] Preferably, the method for high-temperature impurity removal treatment of the ultra-pure carbon black is: commercially available carbon black with a purity of ≥99% is sent into a vacuum furnace, and subjected to high-temperature impurity removal treatment at 1600 degrees under vacuum to obtain ultra-pure carbon black with a purity of ≥99.9%.

[0018] Preferably, the silicon used in the high-temperature siliconizing and sintering treatment is semiconductor silicon with a purity of 99.99% and a particle size of 3 to 5 mm. After the surface coating treatment, the semiconductor silicon is roasted together with the boat support that needs siliconizing treatment in a weight ratio of 15 to 30:100. The surface coating treatment is to add a slurry of ultra-pure carbon black, hexagonal boron nitride, PVP K90 and water during the heating and stirring of the semiconductor silicon, so that a layer of coating is coated on the surface of the silicon particles, a certain amount of moisture is quickly removed, and then it is slowly dried, and then forced to dry at 80°C before being put into the kiln to ensure that there is no moisture and the surface coating is intact.

[0019] Preferably, the impurity removal process uses dilute hydrochloric acid, the concentration is controlled at 8-15%, the temperature is controlled at 20-40° C., and the soaking time is controlled at 20-60 min.

[0020] Preferably, the organic additives are a binder, a dispersant and a defoamer mixed in a mass ratio of (3-5): (6-8): (1-2).

[0021] Preferably, the dispersant is PRODUKT KV 5088;

[0022] The defoamer is CONTRASPUM KWE.

[0023] Preferably, the method for preparing the binder comprises the following steps:

[0024] S1. Completely dissolving polyvinyl butyral in dimercaptopropanol;

[0025] S2, then add thermoplastic resin, nano-silicon dioxide, adipic acid dihydrazide, dibutyl phthalate, hexamethoxymethyl melamine in sequence, raise the temperature to 95-110° C. and mix and stir evenly to prepare a slurry;

[0026] The mass ratio of thermoplastic resin, nano-silicon dioxide, adipic acid dihydrazide, dibutyl phthalate and hexamethoxymethyl melamine is (5-10): (3-5): (1-3): (1-3): (0.5-1.2);

[0027] S3, adding green silicon carbide powder grinding balls, and ball-milling the slurry to obtain a binder.

[0028] Preferably, the thermoplastic resin is selected from one of polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), and polystyrene (PS).

[0029] The present invention can control the content of silicon carbide in the green body after the final reaction and sintering by adjusting the mass ratio of the thermoplastic resin, nano silicon dioxide, adipic acid dihydrazide, dibutyl phthalate and hexamethoxymethylmelamine in the binder component, thereby achieving homogeneous connection of the green body;

[0030] Nano-sized silica as a filler can enhance the mechanical properties of the binder, such as strength, hardness and wear resistance, while improving the thermal stability and aging resistance of the binder; nano-silica is evenly dispersed in the binder through physical interactions with thermoplastic resins or weak interactions such as hydrogen bonds and van der Waals forces, forming a reinforcement effect.

[0031] As a plasticizer, dibutyl phthalate is physically dispersed in thermoplastic resins to reduce the interaction between resin molecules and increase the fluidity of molecular chains, thereby achieving a plasticizing effect. It can give the adhesive flexibility and plasticity, reduce the hardness and glass transition temperature of the adhesive, and enable it to remain soft at low temperatures.

[0032] Adipic acid dihydrazide contains multiple active carbonyl groups and amino groups, which can react with carboxyl groups, hydroxyl groups, etc. in the resin to form a cross-linked network structure, thereby improving the mechanical properties and solvent resistance of the adhesive.

[0033] Hexamethoxymethylmelamine acts as a cross-linking agent and curing agent, giving the adhesive excellent chemical resistance, heat resistance and aging resistance, while improving the mechanical strength and hardness of the adhesive; hexamethoxymethylmelamine can undergo methylation reaction when heated, reacting with hydroxyl groups, carboxyl groups, etc. in the resin to form a cross-linked network structure, increasing the degree of curing and stability of the adhesive.

[0034] The equipment and tools such as mixers, ball mills, pressure grouting machines used in the processes of mud preparation, grouting molding, natural drying, etc. and the parts in contact with the mud are lined with non-metallic linings, which can be stainless steel and polyurethane linings, preferably polyurethane linings; the working environment is controlled at room temperature of 25°C to 35°C, relative humidity of 40% to 50%, and a closed dust-free workshop.

[0035] The hot air drying used is based on an electric heating tube as the heat source. A heat circulation fan and pipeline are installed. A purification adsorber is installed at the pipeline inlet to purify dust, oil, gas, water and other impurities in the circulating hot air.

[0036] The splicing uses mud to bond the parts together to form a complete boat support, and the required mud is the mud used to make the product and is aged for more than 16 hours.

[0037] The high-temperature purification sintering adopts a medium-frequency graphite induction furnace. Before heating, first evacuate to a vacuum degree of less than 5Pa, start heating, add 3 to 4 hours at room temperature to 200℃, evacuate; add 4 to 6 hours at 201 to 900℃, stop evacuating, fill with high-purity nitrogen with a purity of 99.996% to restore normal pressure, start the wax exhaust fan to remove organic matter, and continue to fill with high-purity nitrogen at a rate of 30 to 50ml / min; heat at 900 to 1100℃ for 1 to 2 hours, evacuate; fill with high-purity argon with a purity of 99.996% at 1100 to 2000℃, sinter at normal pressure, and heat for 8 to 9 hours; heat at 2000 to 2300℃ for 8 to 9 hours; keep warm at 2300℃ for 5 hours. After high-temperature purification sintering, the obtained silicon carbide boat support split component blank has an open porosity of 8 to 10%, a strength greater than 100Mpa, and contains a small amount of free carbon.

[0038] The high-temperature siliconizing sintering adopts a vacuum graphite electrode furnace. Before heating, vacuum is first evacuated to a vacuum degree of less than 5Pa, and heating is started. The temperature is from room temperature to 200℃ for 1 to 2 hours, and vacuum is evacuated; the temperature is from 201 to 900℃ for 5 to 6 hours, and vacuum is stopped. High-purity nitrogen is filled to restore normal pressure, and the wax exhaust fan is started to remove organic matter, and high-purity nitrogen is continuously filled at a rate of 80 to 100 ml / min; the heating time is from 900 to 1100℃ for 1 to 2 hours, and vacuum is evacuated; the heating time is from 1100 to 1300℃ for 2 to 3 hours; the heating time is from 1300 to 1500℃ for 3 to 4 hours; the heating time is from 1500 to 1650℃ for 3 to 4 hours; and the temperature is kept at 1650℃ for 2 hours. High-purity nitrogen is filled when cooling down, and the temperature is naturally cooled down.

[0039] A low iron content boat support for photovoltaics and semiconductors manufactured using the above manufacturing method.

[0040] The silicon carbide boat support obtained by the above method has a flexural strength of ≥250Mpa, Fe content ≤5ppm, Ti content ≤5ppm, Mg content ≤3ppm, Zn content ≤2ppm, Al content ≤1ppm, Ca content ≤1ppm, and low impurity content, which can meet the requirements of silicon wafer diffusion process in photovoltaic and semiconductor industries for service life and pollution-free.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The low-iron-content pollution-free silicon carbide boat support manufactured according to the present invention can replace the quartz boat support in the photovoltaic and semiconductor industries. Because of its high compressive strength, excellent thermal conductivity and resistance to rapid cooling and heating, the service life of the boat support is greatly extended; at the same time, it overcomes the fatal weaknesses of traditional reaction-sintered silicon carbide, such as high iron content and serious pollution. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market.

[0045] The high-temperature purification sintering adopts a medium-frequency graphite induction furnace. Before heating, the vacuum is first evacuated to a vacuum degree of less than 5Pa, and heating is started. The vacuum is evacuated at 100°C for 3 hours; the vacuum is evacuated at 500°C for 4 hours, and the vacuum is stopped. High-purity nitrogen with a purity of 99.996% is filled to restore normal pressure. At the same time, the wax exhaust fan is started to remove organic matter, and high-purity nitrogen is continuously filled at a rate of 30ml / min; the heating time is 900°C for 1 hour, and the vacuum is evacuated; the high-purity argon with a purity of 99.996% is filled at 1100°C, and the normal pressure sintering is carried out for 8 hours; the heating time is 2000°C for 9 hours; and the temperature is kept at 2300°C for 5 hours. After high-temperature purification sintering, the silicon carbide boat support split component blank is obtained.

[0046] The high-temperature siliconization sintering adopts a vacuum graphite electrode furnace. Before heating, the vacuum is first evacuated to a vacuum degree of less than 5Pa, and heating is started. The temperature is 200℃ for 2 hours, and vacuum is evacuated; the temperature is 900℃ for 6 hours, and vacuum is stopped. High-purity nitrogen is filled to restore normal pressure, and the wax exhaust fan is started to remove organic matter, and high-purity nitrogen is continuously filled at a rate of 100ml / min; heating at 1100℃ for 2 hours, vacuum is evacuated; heating at 1300℃ for 3 hours; heating at 1500℃ for 4 hours; heating at 1650℃ for 4 hours; and keeping at 1650℃ for 2 hours. High-purity nitrogen is filled when cooling down, and the temperature is naturally cooled down.

[0047] Preparation Example 1

[0048] The preparation method of the binder comprises the following steps:

[0049] S1. Dissolve 100 g of polyvinyl butyral completely in 200 ml of dimercaptopropanol;

[0050] S2, then add 80g of polypropylene resin, 30g of nano-silicon dioxide, 10g of adipic acid dihydrazide, 10g of dibutyl phthalate, and 5g of hexamethoxymethylmelamine in sequence, raise the temperature to 100°C, mix and stir evenly, and prepare a slurry;

[0051] S3. Add green silicon carbide powder grinding balls with an average particle size of 90 μm, and ball-mill the slurry to obtain a binder.

[0052] Preparation Example 2

[0053] The preparation method of the binder comprises the following steps:

[0054] S1. Dissolve 100 g of polyvinyl butyral completely in 200 ml of dimercaptopropanol;

[0055] S2, then add 50g of polypropylene resin, 40g of nano-silicon dioxide, 20g of adipic acid dihydrazide, 10g of dibutyl phthalate, and 10g of hexamethoxymethylmelamine in sequence, raise the temperature to 100°C, mix and stir evenly, and prepare a slurry;

[0056] S3. Add green silicon carbide powder grinding balls with an average particle size of 95 μm, and perform ball milling on the slurry to obtain a binder.

[0057] Preparation Example 3

[0058] The preparation method of the binder comprises the following steps:

[0059] S1. Dissolve 100 g of polyvinyl butyral completely in 200 ml of dimercaptopropanol;

[0060] S2, then add 100g of polypropylene resin, 50g of nano-silicon dioxide, 15g of adipic acid dihydrazide, 20g of dibutyl phthalate, and 10g of hexamethoxymethylmelamine in sequence, raise the temperature to 110°C, mix and stir evenly, and prepare a slurry;

[0061] S3. Add green silicon carbide powder grinding balls with an average particle size of 100 μm, and perform ball milling on the slurry to obtain a binder.

[0062] Example 1

[0063] A method for manufacturing a low-iron-content boat support for photovoltaics and semiconductors comprises the following steps:

[0064] S1. 160 g of raw material, 6 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and dried with hot air to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;

[0065] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;

[0066] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 90 μm, 8 μm and 1.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (30:15:47):2;

[0067] The organic auxiliary agent is a mixture of the binder prepared in Preparation Example 1, the dispersant PRODUKT KV 5088 and the defoamer CONTRASPUM KWE in a mass ratio of 3:6:1;

[0068] S2, putting the semi-finished product in S1 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;

[0069] S3. The split blanks of the silicon carbide boat support are spliced ​​together. After being spliced ​​into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1650°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.

[0070] Example 2

[0071] A method for manufacturing a low-iron-content boat support for photovoltaics and semiconductors comprises the following steps:

[0072] S1. 160 g of raw material, 6 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and dried with hot air to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;

[0073] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;

[0074] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 95 μm, 9 μm and 2 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (32:18:48):2.5;

[0075] The organic auxiliary agent is a mixture of the binder prepared in Preparation Example 2, the dispersant PRODUKT KV 5088 and the defoamer CONTRASPUM KWE in a mass ratio of 3:6:1;

[0076] S2, putting the semi-finished product in S1 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;

[0077] S3. The split blanks of the silicon carbide boat support are spliced ​​together. After being spliced ​​into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1650°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.

[0078] Example 3

[0079] A method for manufacturing a low-iron-content boat support for photovoltaics and semiconductors comprises the following steps:

[0080] S1. 160 g of raw material, 6 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and dried with hot air to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;

[0081] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;

[0082] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 100 μm, 10 μm and 2.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (35:20:50):3;

[0083] The organic auxiliary agent is a mixture of the binder prepared in Preparation Example 3, the dispersant PRODUKT KV 5088 and the defoamer CONTRASPUM KWE in a mass ratio of 3:6:1;

[0084] S2, putting the semi-finished product in S1 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;

[0085] S3. The split blanks of the silicon carbide boat support are spliced ​​together. After being spliced ​​into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1650°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.

[0086] Example 4

[0087] A method for manufacturing a low-iron-content boat support for photovoltaics and semiconductors comprises the following steps:

[0088] S1. 165 g of raw material, 7 g of organic additive and 4 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;

[0089] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;

[0090] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 90 μm, 8 μm and 1.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (32:16:48):2.5;

[0091] The organic auxiliary agent is a mixture of the binder prepared in Preparation Example 1, the dispersant PRODUKT KV 5088 and the defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;

[0092] S2, putting the semi-finished product in S1 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;

[0093] S3. The split blanks of the silicon carbide boat support are spliced ​​together. After being spliced ​​into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1680°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.

[0094] Example 5

[0095] A method for manufacturing a low-iron-content boat support for photovoltaics and semiconductors comprises the following steps:

[0096] S1. 165 g of raw material, 7 g of organic additive and 4 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;

[0097] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;

[0098] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 95 μm, 9 μm and 2 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (32:18:49):2.5;

[0099] The organic auxiliary agent is a mixture of the binder prepared in Preparation Example 2, the dispersant PRODUKT KV 5088 and the defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;

[0100] S2, putting the semi-finished product in S1 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;

[0101] S3. The split blanks of the silicon carbide boat support are spliced ​​together. After being spliced ​​into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1680°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.

[0102] Example 6

[0103] A method for manufacturing a low-iron-content boat support for photovoltaics and semiconductors comprises the following steps:

[0104] S1. 165 g of raw material, 7 g of organic additive and 4 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;

[0105] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;

[0106] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 100 μm, 10 μm and 2.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (35:20:50):3;

[0107] The organic auxiliary agent is a mixture of the binder prepared in Preparation Example 3, the dispersant PRODUKT KV 5088 and the defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;

[0108] S2, putting the semi-finished product in S1 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;

[0109] S3. The split blanks of the silicon carbide boat support are spliced ​​together. After being spliced ​​into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1680°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.

[0110] Example 7

[0111] A method for manufacturing a low-iron-content boat support for photovoltaics and semiconductors comprises the following steps:

[0112] S1. 170 g of raw material, 8 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;

[0113] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;

[0114] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 90 μm, 8 μm and 1.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (30:15:47):2;

[0115] The organic auxiliary agent is a mixture of the binder prepared in Preparation Example 1, the dispersant PRODUKT KV 5088 and the defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;

[0116] S2, putting the semi-finished product in S1 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;

[0117] S3. The split blanks of the silicon carbide boat support are spliced ​​together. After being spliced ​​into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1680°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.

[0118] Example 8

[0119] A method for manufacturing a low-iron-content boat support for photovoltaics and semiconductors comprises the following steps:

[0120] S1. 170 g of raw material, 8 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;

[0121] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;

[0122] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 95 μm, 9 μm and 2 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (33:18:49):2.5;

[0123] The organic auxiliary agent is a mixture of the binder prepared in Preparation Example 2, the dispersant PRODUKT KV 5088 and the defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;

[0124] S2, putting the semi-finished product in S1 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;

[0125] S3. The split blanks of the silicon carbide boat support are spliced ​​together. After being spliced ​​into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1680°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.

[0126] Example 9

[0127] A method for manufacturing a low-iron-content boat support for photovoltaics and semiconductors comprises the following steps:

[0128] S1. 170 g of raw material, 8 g of organic additive and 5 g of pure water are used to prepare slurry in a ball mill, and a slurry injection molding process is used to obtain a blank of the boat support split component. The blank is naturally dried and hot-air dried to remove moisture, and then the blank is trimmed and carved into a semi-finished boat support split component that meets the size requirements;

[0129] The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal;

[0130] The green silicon carbide powder is mixed with green silicon carbide powder of three particle size distributions with average particle sizes of 100 μm, 10 μm and 2.5 μm; wherein the mass ratio of the green silicon carbide powder of the three particle size distributions to the ultrapure carbon black is controlled at (35:20:50):3;

[0131] The organic auxiliary agent is a mixture of the binder prepared in Preparation Example 3, the dispersant PRODUKT KV 5088 and the defoamer CONTRASPUM KWE in a mass ratio of 4:7:1.5;

[0132] S2, putting the semi-finished product in S1 into an induction furnace, and sintering it at a temperature of 2000° C. under the protection of nitrogen gas, and obtaining a green blank of the silicon carbide boat support split component after high-temperature purification and sintering;

[0133] S3. The split blanks of the silicon carbide boat support components are spliced ​​together, and after being spliced ​​into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1700°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.

[0134] Comparative Example 1

[0135] The difference between this comparative example and Example 1 is that the binder prepared in Preparation Example 1 is replaced by a common commercially available OPTAPIXAC112 binder.

[0136] Comparative Example 2

[0137] The difference between this comparative example and Example 1 is that the raw materials are common commercially available green silicon carbide powder and ultrapure carbon black;

[0138] Green silicon carbide powder was purchased from Dongguan Zhuofeng Surface Treatment Materials Co., Ltd., model number 240; ultra-pure carbon black was purchased from Shanghai Kaiyin Chemical Co., Ltd., item number AC80.

[0139] The samples prepared in Examples 1-9 and Comparative Examples 1-2 were tested; the specific experimental data are shown in Table 1:

[0140] Take a sample of 25×25×125mm and use the three-point bending method and an automatic bending tester to test the bending strength of the sample at 1100℃;

[0141] Thermal conductivity adopts GB / T22588-2008 flash method to measure thermal diffusivity or thermal conductivity;

[0142] The porosity adopts the test method of apparent porosity and capacity of porous ceramics in GB / T 1966-1996;

[0143] Abrasion resistance test: refer to GB / T 9867-2008.

[0144] Table 1

[0145]

[0146] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for manufacturing a low iron content boat support for photovoltaic and semiconductor use, characterized in that: The following steps are involved: S1. Prepare slurry by mixing raw materials, organic additives and pure water in a ball mill according to a certain proportion, and obtain a blank of the boat support split component by a slip injection molding process. After the blank is naturally dried and dried with hot air to remove moisture, it is trimmed and carved into a semi-finished boat support split component that meets the size requirements; The raw materials are green silicon carbide powder and ultra-pure carbon black that has been treated with high temperature impurities removal; The organic additive is a mixture of a binder, a dispersant and a defoamer; S2, putting the semi-finished product in S1 into an induction furnace, and sintering it at a temperature of 2000-2300° C. under the protection of an inert gas to obtain a green blank of a silicon carbide boat support split component having an open porosity of 8-10%, a strength greater than 70 MPa, and containing a small amount of free carbon; S3. The split blanks of the silicon carbide boat support are spliced ​​together. After being spliced ​​into a complete boat support, they are sent into a vacuum furnace for high-temperature siliconization and sintering treatment at 1650-1700°C. After being taken out of the kiln, they are subjected to grinding, sandblasting, fine washing, impurity removal, ultrasonic cleaning, and drying processes to obtain a boat support with low iron content.

2. The method for manufacturing a low iron content boat support for photovoltaic and semiconductor use according to claim 1, characterized in that: The mass ratio of the raw material, the organic auxiliary agent and the pure water is (160-170):(6-8):(3-5).

3. The method for manufacturing a low iron content boat support for photovoltaic and semiconductor use according to claim 1, characterized in that: The green silicon carbide powder is mixed with green silicon carbide powder having three particle size distributions of average particle size of 90 to 100 μm, 8 to 10 μm and 1.5 to 2.5 μm; The mass ratios of green silicon carbide powder with three particle size distributions to ultrapure carbon black are controlled within the range of [(30-35):(15-20):(47-50)]:(2-3).

4. The method for manufacturing a low iron content boat support for photovoltaic and semiconductor use according to claim 1, characterized in that: The method for high-temperature impurity removal treatment of the ultra-pure carbon black is as follows: commercially available carbon black with a purity of ≥99% is sent into a vacuum furnace, and subjected to high-temperature impurity removal treatment at 1600 degrees in a vacuum state to obtain ultra-pure carbon black with a purity of ≥99.9%.

5. The method for manufacturing a low iron content boat support for photovoltaic and semiconductor use according to claim 1, characterized in that: The silicon used in the high-temperature siliconizing and sintering treatment is semiconductor silicon with a purity of 99.99% and a particle size of 3 to 5 mm. After the surface coating treatment, the semiconductor silicon is roasted together with the boat support that needs siliconizing treatment in a weight ratio of 15 to 30:

100. The surface coating treatment is to add a slurry of ultra-pure carbon black, hexagonal boron nitride, PVP K90 and water during the heating and stirring of the semiconductor silicon, so that a layer of coating is coated on the surface of the silicon particles, a certain amount of moisture is quickly removed, and then it is slowly dried. Before being put into the kiln, it is forced to be dried at 80°C again to ensure that there is no moisture and the surface coating is intact.

6. The method for manufacturing a low iron content boat support for photovoltaic and semiconductor use according to claim 1, characterized in that: The impurity removal process uses dilute hydrochloric acid, the concentration of which is controlled at 8-15%, the temperature at 20-40° C., and the soaking time at 20-60 minutes.

7. The method for manufacturing a low iron content boat support for photovoltaic and semiconductor use according to claim 1, characterized in that: The organic auxiliary agents are a binder, a dispersant and a defoamer, which are mixed in a mass ratio of (3-5): (6-8): (1-2).

8. The method for manufacturing a low iron content boat support for photovoltaic and semiconductor use according to claim 7, characterized in that: The dispersant is PRODUKT KV 5088; The defoamer is CONTRASPUM KWE.

9. The method for manufacturing a low iron content boat support for photovoltaic and semiconductor use according to claim 1, characterized in that: The preparation method of the binder comprises the following steps: S1. Completely dissolving polyvinyl butyral in dimercaptopropanol; S2, then add thermoplastic resin, nano-silicon dioxide, adipic acid dihydrazide, dibutyl phthalate, hexamethoxymethyl melamine in sequence, raise the temperature to 95-110° C. and mix and stir evenly to prepare a slurry; The mass ratio of thermoplastic resin, nano-silicon dioxide, adipic acid dihydrazide, dibutyl phthalate and hexamethoxymethyl melamine is (5-10): (3-5): (1-3): (1-3): (0.5-1.2); S3, adding green silicon carbide powder grinding balls, and ball-milling the slurry to obtain a binder.

10. A low iron content boat support for photovoltaics and semiconductors manufactured according to the manufacturing method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing transitional metal-doped silicon carbide material through self-propagation high-temperature synthesis

    CN102161587A

  • Charging method of reaction sintered silicon carbide

    CN108706977A

  • Method for preparing siliconizing silicon carbide hot-press casting oven fire-bearing beryllium

    CN110218094A

  • High-purity high-density silicon carbide ceramic and manufacturing method thereof

    CN112159232A

  • Silicon carbide ceramic product and preparation method thereof

    CN112745124A

Cited By

  • Preparation method of silicon carbide boat

    CN120903943A

  • A method for preparing a silicon carbide boat

    CN120903943B